THE SEARCH FOR TRUTH IN THE LEGAL PROCESS AND THE EXTRAJUDICIAL FACTORS IN THE PRODUCTION AND EVALUATION OF ORAL EVIDENCE (ESMAT Magazine, 2024)
This article seeks to analyze whether a scientific standard exists to search for truth in the judicial process, and whether there are criteria to enter into the discussion of potential subjective states in the production and valuation of evidence about controversial facts in a procedural legal relationship. The methodology is theoretical in nature and supported by a qualitative approach. Its criterion is an analysis of the state of the art of the Brazilian forensic practice, particularly regarding parol evidence, associated with knowledge coming from other areas of knowledge.  The goal is to clarity the cognitive limitations of witnesses and the cognitive bias of judges when valuating evidence.
Keywords: Truth; Process; Judicial Behavior; Evidence